PERGESERAN ADAT PERKAWINAN MASYARAKAT MELAYU DESA PEMBATANG KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Masdi, Masdi; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted in Pemtang Village, Pangean District. The purpose of this study is to find out the cultural customs of marriage in Pemtang Village, Pangean District, to find out how the procedures for implementing the marriage customs of the Pemtang Village community, Pangean District, to find out how the role of niniak mamak in the implementation of marriage in Pemtang Village, Pangean District, to find out how the shift in the implementation of marriage customs in the Pemtang Village community, Pangean District. The method used in this research is qualitative. The data obtained from the interviews were then analyzed in their own language. This research began to be carried out from the beginning of the title of this researcher being submitted until this thesis was completed. Data collection techniques used are Observation Techniques, Documentation Techniques, Interview Techniques, and Data Analyst Techniques. The results of this study indicate that there are several forms and conditions of marriage that are prohibited by custom, namely ethnic marriage and pregnancy outside of marriage, the requirements for marriage are in the form of customs and administration.Key Words: Shifting Marriage Traditions